Smartphone Use and Academic Performance: Correlation or Causal Relationship? - Stijn Baert; Suncica Vujic; Simon Amez; Matteo Claeskens; Thomas Daman; Arno Maeckelberghe; Eddy Omey; Lieven De Marez (Institute of Labor Economics (IZA), 2018)
After a decade of correlational research, this study is the first to measure the causal impact of (general) smartphone use on educational performance. To this end, we merge survey data on general smartphone use, exogenous predictors of this use, and other drivers of academic success with the exam scores of first-year students at two Belgian universities. The resulting data are analysed with instrumental variable estimation techniques. A one-standard-deviation increase in daily smartphone use yields a decrease in average exam scores of about one point (out of 20). When relying on ordinary least squares estimations, the magnitude of this effect is substantially underestimated.
Keywords: I21; I23; L86; 330; smartphone use; academic performance; causality